2017
DOI: 10.5114/pg.2017.70469
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood grouping in Egyptian children with rotavirus gastroenteritis

Abstract: IntroductionRotavirus gastroenteritis is an important public health problem all over the world, causing a notable economic burden in both developing and developed countries.AimTo explore the relationship between blood group typing, rotavirus gastroenteritis, and its severity in Egyptian children.Material and methodsA cross sectional case control study was conducted on 231 cases of acute gastroenteritis attending the outpatient clinic of Al-Zahraa University Hospital. Full history taking, clinical examination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
3
18
1
Order By: Relevance
“…Furthermore, a similar finding was recently reported from Pakistan, where secretors with blood type O were more likely to seroconvert compared to non-blood type O individuals 25 , the majority of which were blood type B. Moreover, a recent study from Egypt found that rotavirus positive cases of gastroenteritis were significantly less prevalent in children with blood type B as compared with type A 34 . To our knowledge, the potential of the blood type B phenotype to reduce susceptibility to natural infection with P[8] strains has not yet been reported and further studies are warranted.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, a similar finding was recently reported from Pakistan, where secretors with blood type O were more likely to seroconvert compared to non-blood type O individuals 25 , the majority of which were blood type B. Moreover, a recent study from Egypt found that rotavirus positive cases of gastroenteritis were significantly less prevalent in children with blood type B as compared with type A 34 . To our knowledge, the potential of the blood type B phenotype to reduce susceptibility to natural infection with P[8] strains has not yet been reported and further studies are warranted.…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings were reported in a study carried out in Egypt, where children with blood group A (43%), followed by O (26%), were reported to have the highest prevalence of RV disease [11]. This was attributed to host susceptibility of specific human RV strains and the pathogenesis being influenced by the genetically controlled expression of the different human blood group antigens (HBGAs).…”
Section: Effects Of Abo Blood Grouping On Rotavirus Disease Burden Insupporting
confidence: 86%
“…Mohammadali et al reported that the presence of blood group O might significantly decrease the risk of hepatitis B, and the distribution of Rh in HBV-infected individuals was higher between Rh-positive donors (Mohammadali and Pourfathollah, 2014 ). Elnady et al found that Rota-positive status for rotavirus gastroenteritis was significantly more prevalent among those with blood type A and significantly less prevalent among those with blood type B (Elnady et al, 2017 ). Another recent study carried out by Degarege et al reported that malaria patients with blood group A had a higher risk of anemia than did those with O and non-A phenotypes (Degarege et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%